2006
DOI: 10.1002/pros.20404
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of hormone‐refractory prostate cancer patients with peptide cocktail‐loaded dendritic cells: Results of a phase I clinical trial

Abstract: The described protocol represents a safe and feasible concept for the induction of clinical and immunological responses. The application of a peptide cocktail-derived from different antigens as a novel treatment modality is supposed to allow for the genetic and biologic heterogeneity of PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 48 publications
0
72
1
4
Order By: Relevance
“…Nevertheless, several ion channel modulators are already in clinical use or currently tested in clinical trials [5,141]. Moreover, ion channels are considered as targets for vaccination against tumour-associated antigens [142]. The extracellular domains of the channels and transporters are accessible for antibodies [143].…”
Section: Ion Channels As Drug Targetsmentioning
confidence: 99%
“…Nevertheless, several ion channel modulators are already in clinical use or currently tested in clinical trials [5,141]. Moreover, ion channels are considered as targets for vaccination against tumour-associated antigens [142]. The extracellular domains of the channels and transporters are accessible for antibodies [143].…”
Section: Ion Channels As Drug Targetsmentioning
confidence: 99%
“…While the main aim of this phase I trial was the induction of specifi c immune response, a biochemical response could also be observed in 6 out of 14 patients, who showed a signifi cant decrease in PSA serum levels (30% or more from the baseline) compared to previous studies using antigenpresenting cells loaded with diff erent antigen sources (such as peptides, proteins or mRNA), which reported reductions in serum PSA levels only sporadically (Tjoa et al, 1999;Mu et al, 2005;Fuessel et al, 2006). However, due to the heterogeneity of our patient cohort, we could not discount that the diff erent stages and PSA levels before the treatment may have infl uenced the observed biochemical responses.…”
Section: The Chilean Vaccine Against Prostate Cancer: Re-sultsmentioning
confidence: 85%
“…In another phase I clinical trial, eight patients with hormone-refractory PC received four vaccinations with DC loaded with a cocktail of HLA-A2-restricted peptides derived from PSA, PSMA, surviving, prostein and transient receptor potential p8. 172 It is suggested that vaccination with a cocktail of peptides derived from different antigens might be superior treatment modality due to the genetic and biologic heterogeneity of PC. 172 In a different vaccination approach targeting PAP (Dendreon Corp, Seattle, WA, USA, formerly Activated Cell Therapy), in association with the Mayo Clinic, developed the DC therapy APC8015 (Provenge) for the potential treatment of hormone-refractory PC.…”
Section: Dc-based Pc Vaccinesmentioning
confidence: 99%
“…172 It is suggested that vaccination with a cocktail of peptides derived from different antigens might be superior treatment modality due to the genetic and biologic heterogeneity of PC. 172 In a different vaccination approach targeting PAP (Dendreon Corp, Seattle, WA, USA, formerly Activated Cell Therapy), in association with the Mayo Clinic, developed the DC therapy APC8015 (Provenge) for the potential treatment of hormone-refractory PC. In this approach, DC were isolated from patients with hormonerefractory metastatic PC, loaded ex vivo with a recombinant fusion protein consisting of PAP linked to GM-CSF (designated PA2024), and reinfused into patients.…”
Section: Dc-based Pc Vaccinesmentioning
confidence: 99%